Plectosporium Blight of Cucurbits - J. Stacy Strickland; Gary K. England; Robert J. McGovern (EDIS, 2007)
PP-237, a 4-page illustrated fact sheet by J. Stacy Strickland, Gary K. England, and Robert J. McGovern, discusses this relatively new disease of cucurbits, its disease cycle, symptoms, and management. Includes a table of fungicides recommended for use in pumpkin and squash. Published by the UF Department of Plant Pathology, August 2007.